The Pathogenesis of Cutaneous Lupus Erythematosus Revealed through the Therapeutic Effects of Hydroxychloroquine - Fukumi Furukawa (Advancement and New Understanding in Medical Science Vol. 6, 2024)
In recent years of research in immunology, the understanding of innate immunity has deepened, and the concept of innate immunity has been proposed even in the field of acquired immunity. The conventional immunosuppressive treatments mainly act via regulation of acquired immunity. However, the involvement of innate immunity was confirmed for hydroxychloroquine (HCQ), which has been confirmed to be effective in the treatment of cutaneous lupus erythematosus (CLE). Approximately 1.5 years prior to this trial, HCQ was officially approved for use in Japan by the Japanese Ministry of Health, Labor and Welfare for the treatment of CLE and SLE in September 2015. This review introduces the mechanism underlying the development of CLE from the viewpoint of autoantibodies, cytokines, and innate immunity. Furthermore, the mechanism of action of HCQ is introduced and discussed.